Avalia????o da autoestima de pacientes idosos ap??s a instala????o de pr??teses dent??rias totais sobre implantes - Ferreira, Andrey Carneiro (2016)
The loss of teeth or leakage of dentures in the elderly may compromise the masticatory function the self-esteem and the level of satisfaction with life, and with the installation of dental implants the patient has an improvement on masticatory function and nutritional level. Objective: to evaluate the self-esteem and satisfaction with life of seniors who did dental implant supported prosthesis total in the last 12 months, from rating scales. Materials and methods: transversal descriptive quantitative research with a sample of 21 elderly patients and data analysis were used to test t and X2, average, standard deviations and frequencies. Results: participants presented themselves with high satisfaction with life (p = 0.87) and good selfesteem (p = 0.72), related to the use of prosthesis. Regarding the prostheses. Conclusion: The prostheses are important to the social conviviality, raising self-esteem and well being of the patient and your satisfaction with life, since the patient perform the clinical follow-up and perform periodic maintenance.